2017
DOI: 10.1556/204.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Are opinion leaders more satisfied? Results of a SEM model about the relationship between opinion leadership and online customer satisfaction

Abstract: More and more research is dedicated to address the phenomenon of online word-of-mouth (WOM).Concerning electronic WOM, three major underlying motives can be differentiated: opinion seeking, opinion giving and opinion passing (Flynn et al. 1996, Sun et al. 2006. The main aim of the research is to analyse the relationship between these three dimensions and the level of customer satisfaction.The research is based on a representative sample of 1000 respondents living in Hungary. According to the hypothesized Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
4
0
4
Order By: Relevance
“…Thus, the model suggests that a small group of influencers disseminate information, influencing the opinions of a large number of people (Ertekin and Atik, 2012). Without those opinion seekers, opinion leaders cannot exist and vice versa (Nagy et al , 2017). Besides, both are considered integral to the construct of word of mouth (WOM) (Sun et al , 2006b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the model suggests that a small group of influencers disseminate information, influencing the opinions of a large number of people (Ertekin and Atik, 2012). Without those opinion seekers, opinion leaders cannot exist and vice versa (Nagy et al , 2017). Besides, both are considered integral to the construct of word of mouth (WOM) (Sun et al , 2006b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The internet and social media have provided efficient ways to facilitate the search for and gathering of information for opinion seekers (Nagy et al , 2017). Consumers use the internet to obtain the online opinion of others as a way to reduce risk or to secure lower prices or to obtain pre-purchase information easily (Bertrandias and Goldsmith, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigating consumers’ motivations to provide eWOM helps researchers and practitioners to understand and encourage or discourage information assimilation on the internet, which can influence consumers’ purchase intentions, loyalty and commitment (Dessart et al , 2019; Yan et al , 2018). However, insights from eWOM research on the topic of engagement in eWOM, particularly eWOM providing behaviour, have not always been cumulative and some studies have reported conflicting results about the effect of factors, such as incentives (Hennig-Thurau et al , 2004; Yoo et al , 2013), opinion seeking (Magalhaes and Musallam, 2014; Nagy et al , 2017), involvement (Alhidari et al , 2015; Sohn, 2009), brand attitude (Rialti et al , 2017; Yeh and Choi, 2011), altruism (Horng, 2016; Reimer and Benkenstein, 2016), customer satisfaction (Luarn et al , 2015; Son et al , 2012) and self-enhancement (Magalhaes and Musallam, 2014; Tong et al , 2013) to name a few, on eWOM providing behaviour. Therefore, the aim of this study is to synthesise findings from existing studies on eWOM providing behaviour by using meta-analysis to answer the research question: What factors are related to eWOM providing behaviour?…”
Section: Introductionmentioning
confidence: 99%
“…3 A végleges, banki szolgáltatások esetében használható E-S-Qual és E-RecS-Qual skálát 2017 fő válaszai alapján alkották meg (Akinci et al, 2010).…”
Section: E-s-qual éS E-recs-qual (2005)unclassified
“…A kiegészítő skála átlagos értékei ezektől kissé elmaradnak: legjobb értékelést a válaszadó készség dimenzió kapta (4,4), ezt követi a kapcsolat (4,35), majd a kompenzáció (3,96). Az eredmények az online patika esetében is hasonlóan alakultak.…”
Section: Eredményekunclassified